Software Development For Regional Detention Pond Design Using Visual Basic 6.0 - Case Study On Sungai Air Salak Catchment - Ong, Boon Heng (Universiti Sains Malaysia, 2006)
Nowadays, detention ponds are widely used in controlling flood due to its capacity in storing the additional surface runoff generated from development. The procedures for the estimation and routing of design hydrographs are presented in the Urban Stormwater Management Manual for Malaysia (MSMA). However, the complexity of the calculations and the number of hydrographs that need to be estimated and routed through the basin makes manual calculation methods very wearisome and time consuming. Thus, this study was carried out to develop a computerised modelling using Visual Basic 6.0 to ease and speed up the design process. In order to develop a computerised modelling of a detention pond, the catchment’s area of the Sungai Air Salak was analysed. The study focused on the use of a regional detention pond which can provide satisfactory storage on catchments of more than 80 hectares. In regional detention pond design, Time-Area Method was used to obtain the inflow hydrograph for pre-development and post-development whereas Storage Indication Method was applied to design the pond size as well as the outlet structures. From the study and design that were carried out, a simple and user friendly computer modelling was developed. This system is easy to use and is able to provide an effective detention pond design without having to go through MSMA and design it manually.